2012
DOI: 10.1002/pi.4308
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of toughening mechanisms of polypropylene/ethylene–octene copolymer/maleic anhydride‐grafted poly(ethylene‐co‐octene)/clay nanocomposite

Abstract: The toughness of a polypropylene (PP)/ethylene‐octene copolymer (EOC)/maleic anhydride‐grafted poly(ethylene‐co‐octene) (EOC‐g‐MA)/clay nanocomposite and blends of PP/EOC and PP/EOC/EOC‐g‐MA was investigated using Charpy impact and single‐edge‐notch tensile (SENT) tests. In order to understand the toughening mechanisms, impact fracture surfaces and damage zones of single‐edge‐notch samples were studied with scanning electron microscopy and transmission optical microscopy, respectively. It was observed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Because the modulus and strength of PP/EOC/EOC‐g‐MA/PP‐g‐MA blend are lower than those of PP/EOC while its toughness is higher, it can be concluded that the existence of the compatibilizers have affected the mechanical properties of nanocomposite too. Our previous studies showed adding EOC‐g‐MA exclusively to the PP/EOC blend led to a large enhancement in toughness because of its rubbery nature, the enhanced compatibility, and the reduced crystallinity of the blend. In contrast, the PP‐g‐MA used in this work is detrimental for the mechanical properties of PP/EOC/clay nanocomposite including tensile strength, tensile modulus, and impact strength …”
Section: Resultsmentioning
confidence: 99%
“…Because the modulus and strength of PP/EOC/EOC‐g‐MA/PP‐g‐MA blend are lower than those of PP/EOC while its toughness is higher, it can be concluded that the existence of the compatibilizers have affected the mechanical properties of nanocomposite too. Our previous studies showed adding EOC‐g‐MA exclusively to the PP/EOC blend led to a large enhancement in toughness because of its rubbery nature, the enhanced compatibility, and the reduced crystallinity of the blend. In contrast, the PP‐g‐MA used in this work is detrimental for the mechanical properties of PP/EOC/clay nanocomposite including tensile strength, tensile modulus, and impact strength …”
Section: Resultsmentioning
confidence: 99%
“…This route is also known as compounding, the most versatile, and practical way for modification of physical properties of thermoplastics. Structural, morphological, thermal, and mechanical properties of ternary polyolefin nanocomposites consisting of a polyolefin blend as matrix phase and a nanofiller as reinforcing material have been extensively studied . Moreover, some studies have focused on effects of nanofillers on microstructure formation of immiscible blends, in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…A plastic material simultaneously having high dimensional stability (low CLTE) and a high level of impact resistance is difficult to produce. Hence, incorporating elastomer or rubber is an effective approach to improving impact resistance . However, this incorporation often negatively affects the dimensional precision at high temperatures because the CLTE values of elastomers are higher than those of plastics.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, incorporating elastomer or rubber is an effective approach to improving impact resistance. 2,3 However, this incorporation often negatively affects the dimensional precision at high temperatures because the CLTE values of elastomers are higher than those of plastics. Although a finer dispersion of elastomer domains by enhancing the compatibility among the components may improve the impact resistance for a lower amount of elastomer, 4 the dimensional precision at high temperatures cannot be improved by this approach.…”
Section: Introductionmentioning
confidence: 99%